2008
DOI: 10.1590/s0101-20612008000200026
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de ferro em misturas de alimentos com adição de alimentos com alto teor de vitamina C e de cisteína

Abstract: A anemia ferropriva atinge cerca de 2 bilhões de pessoas no mundo e é causada pelo desequilíbrio na quantidade biodisponível de ferro e sua necessidade orgânica. No Brasil, a anemia ferropriva foi apontada como a segunda maior deficiência causadora de doença na infância (ALMEIDA et al., 2004;SPINELLI et al., 2005).A biodisponibilidade do ferro depende da composição e forma como os alimentos são consumidos e da combinação destes na dieta. O ferro heme presente na carne bovina, peixes, aves e vísceras apresenta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
9

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
2
7
0
9
Order By: Relevance
“…The phytate content of oat flour was found to be 0.74 g (100 g) -1 and that of rice flour 0.55 g (100 g) -1 (GARCÍA-ESTEPA; GUERRA-HERNÁNDEZ; GARCÍA-VILLANOVA, 1999), values higher than found in the non-soaked pequi peel flours. On evaluating the bioavailability of iron in meals consisting of rice, beans, meat and tomato, Fantini et al (2008) reported that the values of 0.09 g (100 g) -1 and 0.2 g (100 g) -1 for Phytic acid played no inhibitory effect.…”
Section: In Vitro Protein and Starch Digestibilitymentioning
confidence: 99%
“…The phytate content of oat flour was found to be 0.74 g (100 g) -1 and that of rice flour 0.55 g (100 g) -1 (GARCÍA-ESTEPA; GUERRA-HERNÁNDEZ; GARCÍA-VILLANOVA, 1999), values higher than found in the non-soaked pequi peel flours. On evaluating the bioavailability of iron in meals consisting of rice, beans, meat and tomato, Fantini et al (2008) reported that the values of 0.09 g (100 g) -1 and 0.2 g (100 g) -1 for Phytic acid played no inhibitory effect.…”
Section: In Vitro Protein and Starch Digestibilitymentioning
confidence: 99%
“…In our study, the quantity of DF was 5%. According to Fantini et al (2008), DF does not affect mineral utilization such as iron, and whole cereals have inhibitory effect only due to the fact that they have phytate in their composition.…”
Section: Discussionmentioning
confidence: 99%
“…The hemicellulose fraction of dietary fiber can uptake metal ions due to formation of bonds with carboxylic groups of uronic acids and/or hydroxyl groups (Nawirska & Uklańska, 2008). However, the DF itself does not significantly influence iron absorption; the inhibitory effect of cereal bran is attributed almost totally to its high phytate content (Fantini et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Apesar da grande variação observada, o tomate seco pode ser considerado boa fonte de ferro, superando a maioria dos vegetais, inclusive o feijão cozido. Além disso, a presença de vitamina C no tomate seco potencializa a absorção do ferro não heme, pois mantém o ferro no estado ferroso e forma o quelato ferro-ascorbato que apresenta boa solubilidade, aumentando sua biodisponibilidade (OSÓRIO, 2002;FANTINI et al, 2008). Verifi cou-se grande diferença entre o teor de enxofre dos produtos avaliados.…”
Section: Tabela 1 -Características Físicas E Químicas De Tomates Secounclassified